البنية السردية في رواية زينب لمحمد حسين هيكل أنموذجا - قطاي, فاطمة (كلية الأدب العربي والفنون, 2025)
هذه الدراسة الأكاديمية هي ثمرة جهد تهدف إلى أن تكون مرجعًا مفيدًا، ولو قليلاً، لمن سيأتون بعدي. وقد تم تحقيق ذلك من خلال تسليط الضوء على البنية السردية في رواية زينب لمحمد حسين هيكل. تدرس البنية السردية الرواية من خلال الشخصيات، والأحداث، والزمن، والمكان. وقد اعتمدتُ في دراستي على فصلين يسبقهما مدخل بعنوان «ضبط المصطلحات والمفاهيم». و يحمل الفصل الأول عنوان: «العَتبات النصية في رواية زينب». وقد تطرقتُ فيه إلى سيرة ذاتية للمؤلف محمد حسين هيكل، والبنية الخارجية للرواية، بالإضافة إلى قراءة في عنوان الرواية. أما الفصل الثاني فبعنوان: «عناصر البنية السردية وتجلياتها في رواية زينب». تناولتُ فيه مفهوم الشخصيات، وأنواعها، وأهميتها في الرواية. وتناولت في القسم الثاني مفهوم الزمن، وأنواعه، وأهميته، وأخيرًا بنية المكان، وأنواعه في الرواية، وأهميته. This academicstudyis the result of an effort aimed at serving as a usefulreference, even if only to a smallextent, for thosewho come after me. This has been achieved by shedding light on the narrative structure in the novelZaynab by Mohamed Hussein Heikal. The narrative structure isexaminedthrough the characters, events, time, and space. Mystudyisbased on twochapters, preceded by an introduction entitled "Clarification of Terms and Concepts." The first chapter istitled: "The TextualThresholds in the NovelZaynab." In it, I addressed the biography of the author Mohamed Hussein Heikal, the external structure of the novel, in addition to an analysis of the novel’stitle. The second chapteristitled: "Elements of Narrative Structure and Their Manifestations in the NovelZaynab." In thischapter, I explored the concept of characters, their types, and theirsignificance in the novel. In the second section, I discussed the concept of time, its types, and its importance; finally, I examined the structure of space, its types within the novel, and itssignificance.
Keywords: العتبات النصية- رواية زينب- البنية السردية- محمد حسين هيكل; • Paratextual elements • Zaynab novel • Narrative structure • Muhammad Husayn Haykal